Pengaruh Pengungkapan ESG Dan Good Corporate Governance Terhadap Kinerja Keuangan: Bukti Empiris Peran Moderasi ESG Investors Dan Good Corporate Governance - Esa Virjinia Ririanti; Ida Nur Aeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the impact of Environmental, Social, and Governance Disclosure and Good Corporate Governance on corporate financial performance, as well as to examine the role of ESG investors as a moderating variable. In this study, GCG is proxied by independent commissioners and audit committees, while financial performance is measured using ROA. This study employs a quantitative approach using secondary data obtained from financial statements, annual reports, and sustainability reports of companies in the basic and chemical industries listed on the Indonesia Stock Exchange for the period 2022–2024. The study sample consists of 22 companies with a total of 66 observations selected using purposive sampling. Data analysis in this study was conducted using EViews 12. The analytical methods employed include multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that ESG disclosure and the audit committee do not have a significant effect on financial performance, whereas independent directors have a positive and significant effect. Furthermore, ESG investors only moderate the relationship between the audit committee and financial performance, but do not moderate the relationship between ESG disclosure and independent directors on financial performance. These findings suggest that internal oversight mechanisms through independent directors are more effective in improving financial performance compared to ESG practices. This study provides empirical evidence regarding the importance of strengthening corporate governance and improving the quality of ESG implementation in supporting corporate financial performance.